THE ROLE OF STRUCTURALISM IN TOWN PLANNING RESEARCH IN THE DIGITAL ARCHITECTURE ERA - Albertus Sidharta Muljadinata, M.T. (Universitas Katolik Soegijapranata, 2022)
At first, Structuralism developed rapidly in France, but structuralism was not yet known in Indonesia; even in the early 1990s, Lévi-Strauss' structuralism did not resonate with Indonesian socio-cultural scientists. In 1966 the publication of the book The Architecture of the City, authored by Aldo Rossi, provided input on architectural and urban research based on structuralism; This book teaches Typomorphology. The purpose of this study is to provide an explanation of how structuralism is used as an approach method in town planning research. There are two research methods used, the first is a literature review method to gain an understanding of structuralism and the use of structuralism in the field in the context of town planning, namely the typomorphology approach. After this understanding, followed by the second research method, namely the case study method, which is to explain the use of the structuralism method in case studies in Semarang City. The research provides an understanding of structuralism, and an understanding of the use of structuralism in the scope of architecture, particularly in town planning research. In the current era of digital architecture, the results of this study provide an overview of the important role of structuralism in contributing to the facts of all aspects that make up the city; and this is the basis for research on urban development using digital architectural technology.